45. Сводим к общему знаменателю
0" alt=" \displaystyle \frac{(2a-3b)^2(2a+3b)^2-8a^2(2a^2-9b^2)}{(2a+3b)^2}=\frac{(4a^2-9b^2)^2-8a^2(2a^2-9b^2)}{(2a+3b)^2} =\\ \\ =\frac{16a^4-72a^2b^2+81b^4-16a^4+72a^2b^2}{(2a+3b)^2}=\frac{81b^4}{(2a+3b)^2}>0" align="absmiddle" class="latex-formula">
Получили, что выражение
принимает неотрицательные значения.
46. 1) ![\displaystyle \frac{3}{(x-3)(x+4)}=\frac{a}{x-3}+\frac{b}{x+4}=\frac{a(x+4)+b(x-3)}{(x-3)(x+4)} \displaystyle \frac{3}{(x-3)(x+4)}=\frac{a}{x-3}+\frac{b}{x+4}=\frac{a(x+4)+b(x-3)}{(x-3)(x+4)}](https://tex.z-dn.net/?f=+%5Cdisplaystyle+%5Cfrac%7B3%7D%7B%28x-3%29%28x%2B4%29%7D%3D%5Cfrac%7Ba%7D%7Bx-3%7D%2B%5Cfrac%7Bb%7D%7Bx%2B4%7D%3D%5Cfrac%7Ba%28x%2B4%29%2Bb%28x-3%29%7D%7B%28x-3%29%28x%2B4%29%7D++++)
![3=a(x+4)+b(x-3) 3=a(x+4)+b(x-3)](https://tex.z-dn.net/?f=+3%3Da%28x%2B4%29%2Bb%28x-3%29+)
Пусть x=-4, то ![3=b(-4-3)~~\Rightarrow~~~ b=-\frac{3}{7} 3=b(-4-3)~~\Rightarrow~~~ b=-\frac{3}{7}](https://tex.z-dn.net/?f=+3%3Db%28-4-3%29%7E%7E%5CRightarrow%7E%7E%7E+b%3D-%5Cfrac%7B3%7D%7B7%7D++)
Пусть x=-3, то ![3=a(3+4)~~~\Rightarrow~~~ a=\frac{3}{7} 3=a(3+4)~~~\Rightarrow~~~ a=\frac{3}{7}](https://tex.z-dn.net/?f=+3%3Da%283%2B4%29%7E%7E%7E%5CRightarrow%7E%7E%7E+a%3D%5Cfrac%7B3%7D%7B7%7D++)
Ответ: a = 3/7; b = -3/7.